2006
DOI: 10.1121/1.2146086
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal vibration frequencies of steadily whirling rods

Abstract: Past researchers suggested that "static instabilities" exist at certain rotational speeds of whirling rods. This paper shows these instabilities are an artefact of the material constitutive laws that are being used well outside their range of applicability. An alternative approach is developed where strains due to rotation are separated from the superimposed vibration. This enables the generally predicted lowering of longitudinal natural frequencies with rotational speed shown to be simply a result of the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[1], although their proof did not mention about the subintervals division when a Taylor series representation is not valid in the whole domain of interval ½0; L.…”
Section: Existence and Uniqueness Of Solutionmentioning
confidence: 95%
See 1 more Smart Citation
“…[1], although their proof did not mention about the subintervals division when a Taylor series representation is not valid in the whole domain of interval ½0; L.…”
Section: Existence and Uniqueness Of Solutionmentioning
confidence: 95%
“…However, only a small number of researchers had attempted to formulate and solve rotating rods or beams problems coupled with Coriolis effect. Recently, results obtained by Shum and Entwistle [1] showed that natural frequencies of axial vibration were decreasing for an increasing angular velocity of steadily whirling rods without Coriolis effect by applying receptance approach. More previously, Bhuta and Jones [2] analysed the axial vibration of a rotating bar problem under the small strain assumption.…”
Section: Introductionmentioning
confidence: 98%
“…In those analyses (Bhuta and Jones, 1963;Brunelle, 1971) Lagrangian coordinates were used. Shum and Entwistle (2006) reported that the linear uniaxial model is not representative for the situation at larger strains due to higher angular velocity. The axial deformation of rotating rods was investigated (Hodges and Bless, 1994) by using two simpler nonlinear strain energy models.…”
Section: Introductionmentioning
confidence: 99%
“…The present study attempts to solve the more complicated practical engineering problem of calculating the reference pretension forces of a cable-stayed bridge. A simple two-dimensional cable-stayed bridge is set up and a collocation method based on the complete function solution previously developed by Shum and Entwistle (2006) is used to calculate the stay cable forces.…”
Section: Introductionmentioning
confidence: 99%